Effect of matrix composition on the performance of calcium carbonate filled poly(lactic acid)/poly(butylene adipate-co-terephthalate) composites - Guo Zhenyu; Song Weiqiang; Wei Xueqin; Feng Yu; Song Yixuan; Guo Zidong; Cheng Wenxi; Miao Wei; Cheng Bo; Song Shiping (e-Polymers, 2023)
The ratio of poly(lactic acid) (PLA), poly(butylene adipate-co-terephthalate) (PBAT), and calcium carbonate (CaCO3) fillers in PLA/PBAT/CaCO3 composites was set at 90/10/5, 70/30/5, and 30/70/5. The effect of nano- and micro-CaCO3 on the melting and crystallization performance of the composites was investigated by differential scanning calorimetry. PLA crystallization was related to the PLA and PBAT ratio, cooling rate, and CaCO3 particle size in PLA/PBAT/CaCO3 composites. Nano-CaCO3 prevented the crystallization of PLA in PLA/PBAT/CaCO3 90/10/5 and 70/30/5 but did not prevent the crystallization of PLA in PLA/PBAT/CaCO3 30/70/5. Unlike nano-CaCO3, micro-CaCO3 did not prevent PLA crystallization regardless of the PLA and PBAT ratio. Nano- and micro-CaCO3 enhance PLA90 and PLA70 to some extent, due to the aggregation and dissociation of the CaCO3 filler in polylactic acid. But nano- and micro-CaCO3 improved the mechanical properties of PLA30 several times, due to the good compatibility of the CaCO3 filler and PBAT. The effect of nano-CaCO3 and micro-CaCO3 on the mechanical properties of PLA/PBAT/CaCO3 composites had no significant difference.